1985
DOI: 10.1056/nejm198503143121103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screening for Hemophilia A (Classic Hemophilia) with a Polymorphic DNA Probe

Abstract: We have developed a new method of screening for hemophilia A in families at risk for the disease. A DNA probe (St14) that detects a very polymorphic region on the human X chromosome has been shown to be closely linked to hemophilia A. We observed no recombination between the St14 locus and hemophilia A in 12 families studied. The odds in favor of linkage are 4.4 X 10(9) to 1 (lod score, 9.65). The 95 per cent confidence interval for the probability of a recombination between St14 and hemophilia A is 0 to 6.5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(47 citation statements)
references
References 23 publications
2
42
0
3
Order By: Relevance
“…The following polymorphic markers were used to determine the parental origin of the factor VIH gene inversion: BcR from intron 18 (23), (CA) n microsatellite repeat in intron 13 (24), (CA) n microsatellite repeat in intron 22 (25), Xbal polymorphic site in intron 22 (26), Bgia site of locus DXS15 (27), and the VNTR polymorphisms at loci DXS52 detected by Taql (28). Information concerning the oligonucleoode primers or the hybridization probes for the detection of these polymorphisms can be found in the Genome Data Base.…”
Section: Polymorphic Markersmentioning
confidence: 99%
“…The following polymorphic markers were used to determine the parental origin of the factor VIH gene inversion: BcR from intron 18 (23), (CA) n microsatellite repeat in intron 13 (24), (CA) n microsatellite repeat in intron 22 (25), Xbal polymorphic site in intron 22 (26), Bgia site of locus DXS15 (27), and the VNTR polymorphisms at loci DXS52 detected by Taql (28). Information concerning the oligonucleoode primers or the hybridization probes for the detection of these polymorphisms can be found in the Genome Data Base.…”
Section: Polymorphic Markersmentioning
confidence: 99%
“…Some RFLP markers which could incorporate with the loci corresponding to genetic diseases have been used for researches on sex-linked recessive diseases such as Duchenne muscular dystrophy and fragile X chromosome syndrome. Oberle et al (1985a) reported a new polymorphic probe named ST 14 that has been mapped to the Xq26-28 region. The relative order of the genetic marker loci in X27-qter region is most likely "cen-... 52A--FIX--ST14,DX13" (Drayna et al, 1984) or "cen-...FIX--FVIII--DX13,ST14--Xqter" (Tantrabahi et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…have already been observed (Oberle et al, 1985a). The ST 14-1 probe (3.0 kb EcoRI fragment) is one of the ST 14 fragments which reveals at least 8 allelic fragments ranging from 6.6 kb to 3.4 kb (Oberle et al, 1985b).…”
Section: Subjectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although methods for the direct detection of pathogenic mutations such as factor VIII intron 22 gene inversions have been developed recently (Lakich et al 1993;Pieneman et al 1995), indirect gene analysis using DNA polymorphisms still plays an important role in the carrier detection and prenatal diagnosis of hemophilia A. Many polymorphic markers within or near the factor VIII gene have been reported as being useful for the carrier detection and prenatal diagnosis of hemophilia A: BclI/intron 18 polymorphism (Gitschier et al 1985), XbaI/ intron 22 polymorphism (Wion et al 1986), intron 13/22 dinucleotide repeat polymorphisms (Lalloz et al 1991), and extragenic St14 variable number of tandem repeats (VNTR) located at 4 cM from the factor VIII gene (Oberle et al 1985;Richards et al 1991). The polymerase chain reaction (PCR) has made DNA polymorphism analysis simpler and more rapid for clinical applications than Southern blot analysis, and it can be applied in the analysis of most polymorphisms linked to the factor VIII gene.…”
Section: Introductionmentioning
confidence: 99%